An Illuminated Armenian Manuscript “Guidebook” to the Sacred Shrines in the Holy Land from the End of the Seventeenth Century - Mikayel Arakelyan (Études Arméniennes Contemporaines, 2017)
The Nkaragrutʻiwn Tnōrinakan tełeacʻ is the name given to the collection of manuscripts containing descriptions of monuments located in Palestine, primarily those considered Christian holy places. Closely resembling modern travel books or tourist guides to archeological sites, these manuscripts were compiled with the intent of acquainting Armenian pilgrims with the Sacred Shrines in the Holy Land during the seventeenth and eighteenth centuries. One particular Armenian manuscript, housed in the monastic library of the Mekhitarist Fathers in Vienna, is a very interesting and important “guidebook”, richly illustrated and written by the monk Eremia of Adana at the Holy Sepulchre Church in Jerusalem in 1697. The manuscript contains travel information regarding 80 sites, complete with 81 pictorial compositions. Most of the depictions are of Christian holy places, but there are also a number of representations of Jewish and Muslim sites. Eremia offers a comprehensive guided tour of each of these monuments which during his time were scattered over the territory of Palestine, with many still being in existence today. The proposed subject has tremendous significance for Armenologists and Byzantinologists in the fields of miniature art, iconography, geography, topography, archeology, and history of pilgrimage to the Holy Land.